Characterization of CuCrO2 Material Produced Using Sol-Gel Method - Delviya Amisha; Humaidi, Syahrul; Imaddudin, Agung (Journal of Technomaterial Physics, 2023)
This study aimed to analyze CuCrO2 material produced using the sol-gel method. The characterization used is X-ray Diffraction (XRD) and Scanning Electron Micoscope-Energy Dispersive Spectroscopy (SEM-EDS). The sample was made by weighing the raw material and measuring the solution with a measuring cup according to stoichiometric calculations, then dissolving it, burning it, grinding it, calcining it, sintering it, forming it into pellets, and re-sintering it. The XRD results show that the main phase of the sample is CuCrO2 and impurities (CuCr2O4). From the SEM results, the average particle size is 155.948Âµm.